The Transcriptome and Flux Profiling of Crabtree‐Negative Hydroxy Acid‐Producing Strains of Saccharomyces cerevisiae Reveals Changes in the Central Carbon Metabolism. Issue 9 (17th May 2019) - Jessop‐Fabre, Mathew M.; Dahlin, Jonathan; Biron, Mathias B.; Stovicek, Vratislav; Ebert, Birgitta E.; Blank, Lars M.; Budin, Itay; Keasling, Jay D.; Borodina, Irina
Abstract : Saccharomyces cerevisiae ( S. cerevisiae ) is the yeast cell factory of choice for the production of many biobased chemicals. However, it is a Crabtree‐positive yeast and so shuttles a large portion of carbon into ethanol. Ethanol formation can be eliminated by deleting pyruvate decarboxylase (PDC) activity. It is not yet well understood how PDC‐negative yeasts are affected when engineered to produce other products than ethanol. In this study, pathways are introduced for the production of three hydroxy acids (lactic, malic, or 3‐hydroxypropionic acid [3HP]) into an evolved PDC‐negative strain. These strains are characterized via transcriptome and flux profiling to elucidate the effects that the production of these hydroxy acids has on the host strain. Expression of lactic and malic acid biosynthesis pathways improved the maximum specific growth rate (μmax ) of the strain by 64% and 20%, respectively, presumably due to nicotinamide adenine dinucleotide regeneration. All strains show a very high flux ( > 90% of glucose uptake) into the oxidative pentose phosphate pathway under batch fermentation conditions. The study, for the first time, directly compares the flux and transcriptome profiles of several hydroxy acid‐producing strains of an evolved PDC‐negative S. cerevisiae and suggests directions for future metabolic engineering. Abstract : Yeast Saccharomyces cerevisiae holds great potential as a host organism for the industrial production of organic acids, an industrially relevant class of chemicals. In this work, the authors investigate metabolic fluxes and transcriptional profiles of Crabtree‐negative yeast strains engineered to produce three different hydroxy acids. The results provide guidance for further improvement of hydroxy acid production in yeast.